Fluidized bed CaO hydration-dehydration cycles for application to sorption-enhanced methanation. Issue 9 (2nd September 2019) - Coppola, A.; Massa, F.; Salatino, P.; Scala, F.
ABSTRACT: A sorption-enhanced methanation concept has been recently presented, which is based on the employment of a sorbent able to capture in situ the H2 O produced during the methanation reaction, in order to shift the equilibrium towards the formation of methane. In this work CaO, derived from natural limestone, was tested as a possible sorbent material for H2 O capture in a novel configuration based on the concept of chemical looping in dual interconnected fluidized bed systems. The lab-scale experimental campaign was focused on the study of the sorbent performance in terms of hydration and dehydration cycles at different operating conditions relevant for catalytic methanation. The effect of temperature on the sorbent performance, as well the presence of CO2 in the reaction environment, were investigated. The results showed that CaO has good capacity to capture and release steam in the temperature range of interest. Unfortunately, even at the lowest temperatures tested, the sorbent is affected by the presence of CO2 that worsen its performance in terms of H2 O capture capacity.